Blood loss and transfusion requirements in total joint arthroplasty. - Clarke, A. M. (Royal College of Surgeons of England, 1992)
We report a prospective trial of 100 consecutive patients undergoing primary total hip or knee arthroplasty in order to assess their blood transfusion requirements amid recent fears of the transmission of viruses, particularly hepatitis C, from donor to recipient. Of the patients, 84% were transfused one or more units of blood in the perioperative period and the mean percentage blood loss per replacement represented 30% or less of their estimated circulating blood volume. We suggest that with preoperative blood volume calculations and haemoglobin concentrations, a more cautious approach to blood transfusion should be employed when other blood volume expanders would suffice. We believe, firstly, that where blood losses of 30% or less of the blood volume occur, blood transfusion is not always required in patients with high haemoglobin concentrations and large blood volumes. Secondly, cross-matching should be undertaken according to the individual patient's estimated needs, rather than to a group as a whole.